New Routes for Preparation and Characterization of [Au2(CºN)2P(Ph)2CH2P(Ph)2] Complex - H. Jaafar, Mohammed; Al-Ohaly, A.A. (Asian Journal of Chemistry, 2012)
The gold complex i.e., [Au2(CºN)2P(Ph)2CH2P(Ph)2] has been successfully produced by three reactions, the reaction of polymeric gold cyanide [Au(CN)]n with a suspension of bis(diphenylphosphino)methane (dppm), in acetone in a 2:1, pure ammonia (NH3), [Au(CºN)]n and (Ph)2PCH2P(Ph)2 in acetone in a 2:2:1 or that of [Au(CºN)(NH3)2] with (Ph)2PCH2P(Ph)2 in acetone in a 1:0.5 giving a white precipitate collected as Au2(CºN)2P(Ph)2CH2P(Ph)2. The complex was characterized by elemental analysis, FT-IR and NMR spectroscopy and found in agreement with the proposed formula C27H22N2P2Au2.